2018
DOI: 10.1002/jper.18-0334
|View full text |Cite
|
Sign up to set email alerts
|

A novel Bruton's tyrosine kinase inhibitor, acalabrutinib, suppresses osteoclast differentiation and Porphyromonas gingivalis lipopolysaccharide‐induced alveolar bone resorption

Abstract: Background Periodontitis is not only one of the most prevalent inflammatory diseases among adults, but also commonly linked to numerous systemic conditions including cardiovascular diseases, stroke, and diabetes. Although osteoclasts are responsible for the alveolar bone resorption during periodontitis pathogenesis, the development of pharmacologic strategies targeting these cells has not been vastly fruitful. Methods Bone marrow macrophages were cultured in the presence of macrophage‐colony stimulating factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Recently, another BTK inhibitor, acalabrutinib (ACP-196), has been evaluated for its potential to prevent alveolar bone loss in experimental periodontitis. 157 In this study, mice that received intragingival injections of P. gingivalis-derived lipopolysaccharide were also given intraperitoneal injection of acalabrutinib (0.5 mg/kg on days 1, 4 and 7 postligature placement). The results showed that BTK inhibitor ACP-196 altered osteoclastogenesis and significantly decreased alveolar bone loss by approximately 50% compared with controls.…”
Section: Caspase-1mentioning
confidence: 99%
“…Recently, another BTK inhibitor, acalabrutinib (ACP-196), has been evaluated for its potential to prevent alveolar bone loss in experimental periodontitis. 157 In this study, mice that received intragingival injections of P. gingivalis-derived lipopolysaccharide were also given intraperitoneal injection of acalabrutinib (0.5 mg/kg on days 1, 4 and 7 postligature placement). The results showed that BTK inhibitor ACP-196 altered osteoclastogenesis and significantly decreased alveolar bone loss by approximately 50% compared with controls.…”
Section: Caspase-1mentioning
confidence: 99%
“…BTK is expressed in osteoclasts and is essential for RANKL-induced osteoclast differentiation (Lee et al, 2008). Both ibrutinib and acalabrutinib potently inhibit RANKL-induced osteoclast differentiation in in vitro cultured bone marrow-derived monocytes/macrophages (BMMs) or RAW264.7 cells via the RANK-BTK-PLCγ1/γ2-NF-ATc1 pathway (Shinohara et al, 2014;Pokhrel et al, 2019;Liu et al, 2021). Acalabrutinib also inhibits LPS-induced osteoclast differentiation from RANKL-primed osteoclast precursors via the TLR4-BTK-NF-ATc1/c-Fos pathway (Pokhrel et al, 2019).…”
Section: Osteoclastsmentioning
confidence: 99%
“…Both ibrutinib and acalabrutinib potently inhibit RANKL-induced osteoclast differentiation in in vitro cultured bone marrow-derived monocytes/macrophages (BMMs) or RAW264.7 cells via the RANK-BTK-PLCγ1/γ2-NF-ATc1 pathway (Shinohara et al, 2014;Pokhrel et al, 2019;Liu et al, 2021). Acalabrutinib also inhibits LPS-induced osteoclast differentiation from RANKL-primed osteoclast precursors via the TLR4-BTK-NF-ATc1/c-Fos pathway (Pokhrel et al, 2019). Both ibrutinib and acalabrutinib can significantly reduce the bone-resorbing activities of osteoclasts following treatment with RANKL and M-CSF (Shinohara et al, 2014;Pokhrel et al, 2019).…”
Section: Osteoclastsmentioning
confidence: 99%
See 1 more Smart Citation
“…65 The BTK inhibitor ibrutinib (PCI-32765, Imbruvica) is a FDAapproved drug for the treatment of various B cell cancers. Recently, another BTK inhibitor, acalabrutinib (ACP-196), has shown to prevent alveolar bone loss 66 indicating its possible role in treating periodontal diseases. 3.…”
Section: Blocking Inflammasome Componentsmentioning
confidence: 99%